Development of resistive humidity sensor based on 3D ZnO NRS: MoS2 for real time monitoring of transformer insulation oil - Lee, Yongbeom; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2020)
A resistive humidity sensor was developed based on 3 dimensional (3D) ZnO nanorods (NDs):MoS2 sensing film and wheatstone bridge circuitry for real time monitoring of transformer insulation oil. Wheatstone bridge circuitry was employed to minimize interference due to ambient temperature changes, and 3D sensing film to enhance the sensitivity and the minimum detection resolution. A thick SiO2 passivation layer was covered all 3D structures except for the sensing film to eliminate any contacts with transformer insulating oil during measurement for the purpose of long term stability. The process for the 3D ZnO:MoS2 structures was optimized by varying the solution composition ratio, temperature, and growth time. The completed sensors were characterized in both air and oil and then its properties were compared. The evaluated sensitivity of the sensor in the air was about 15 mV/%RH, and little changes are observed with respect to ambient temperature variations. The sensitivity of the sensor in oil was evaluated to be about 6.8 mV/%RH, slightily lower than the one in air. Long term stability in the sensor performances and high sensing resolution were observed from the developed sensor.
Keywords: Ambient temperature change; Detection resolutions; Long term stability; Real time monitoring; Resistive humidity sensor; Solution composition; Temperature variation; Transformer insulation oil; Humidity sensor; Resistive sensor; Transformer oil; Wheatstone bridge; ZnO Nanorods